OTOMATISASI ADMINISTRASI KEPENDUDUKAN BERBASIS WEB - Fahri Hamdani; Eri Sasmita Susanto; Wawa Marisa (JURNAL TEKNOLOGI INFORMATIKA DAN KOMPUTER, 2024)
Abstract: This study aims to design and build a Web-Based Population Automatic Archive Application for the Brang Kolong Village Office which can facilitate village officials in archiving population data. However, the system still does not have features designed for archiving population data, with the Web-Based Population Auto-Archive Application it can facilitate the process of archiving population data. As well as being a storage medium for data and information about population data. Web-based applications are built using the help of the PHP language and MySQL database using Laravel as a framework. System planning uses object-oriented methods by defining UML designs such as Use Cases, Activity Diagrams, Sequence Diagrams, and Class Diagrams. And tested using the BlackBox Testing method